2017
DOI: 10.1177/1010428317712592
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated fibroblasts secrete FGF-1 to promote ovarian proliferation, migration, and invasion through the activation of FGF-1/FGFR4 signaling

Abstract: Ovarian cancer is the most lethal gynecologic malignancy, due to its high propensity for metastasis. Cancer-associated fibroblasts, as the dominant component of tumor microenvironment, are crucial for tumor progression. However, the mechanisms underlying the regulation of ovarian cancer cells by cancer-associated fibroblasts remain little known. Here, we first isolated cancer-associated fibroblasts from patients' ovarian tissues and found that cancer-associated fibroblasts promoted SKOV3 cells' proliferation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 32 publications
3
64
0
Order By: Relevance
“…However, our results also suggest that Fgf2 is not the only Fgf secreted in the tumour microenvironment as Fgfr blocking was more efficient in reducing tumour colonies than eliminating Fgf2 alone, although a direct effect of the aptamer or Fgfr blocker on the epithelial cells cannot be excluded. Indeed, other Fgf s including Fgf1 and Fgf3 have been shown to promote tumour progression in various cancers . We also showed that in our model, CAFs produce more collagen, recruit TAMs, and promote their switch to the pro‐tumorigenic M2 phenotype.…”
Section: Discussionsupporting
confidence: 66%
“…However, our results also suggest that Fgf2 is not the only Fgf secreted in the tumour microenvironment as Fgfr blocking was more efficient in reducing tumour colonies than eliminating Fgf2 alone, although a direct effect of the aptamer or Fgfr blocker on the epithelial cells cannot be excluded. Indeed, other Fgf s including Fgf1 and Fgf3 have been shown to promote tumour progression in various cancers . We also showed that in our model, CAFs produce more collagen, recruit TAMs, and promote their switch to the pro‐tumorigenic M2 phenotype.…”
Section: Discussionsupporting
confidence: 66%
“…This data suggests that the CAF may produce soluble factors in the medium to promote NSCLC cell survival under stress of chemotherapy drugs. To further determine the key factors in the CAF‐secreted cytokines involved in NSCLC drug resistance, we screened the expression of IGF2 , SDF‐1 , HGF , VEGF α, FGF , EGF , PDGF , CTGF , Tenascin , TSP‐1 and Fibronectin in the CAF pre‐co‐cultured with or without LCP1 cells and found that IGF2 , VEGFa and EGF were significantly upregulated, especially the IGF2 (Figure C). Moreover, we used the recombinant IGF2 to pre‐treat LCP1 and A549 cells, followed by cisplatin, etoposide and vinorelbine diatrate treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, mice treated with IFN-␣ showed a weaker response to oncolytic alphavirus M1 treatment (46). These results may be extrapolated to FGFs, as the expression of various FGFs is upregulated in ovarian cancer, breast cancer, prostate cancer, and colon cancer (47)(48)(49)(50)(51). In tumor microenvironments with high FGF levels, replication of oncolytic VSV or coxsackievirus is possibly naturally inhibited.…”
Section: Discussionmentioning
confidence: 97%